Quality management in Asian universities: lessons from the European and American universities - Asimiran, Soaib; Njie, Baboucarr (Atlantis Press, 2018)
Quality management has taken ascendancy in the universities in particular due, inter alia, to the loss of their status as ivory towers. Hence, quality management in universities takes prominence over several other initiatives. Attention is not only drawn on whether it is primed in universities but also on its practicability and the mechanism for gauging how it is performing. The first pronouncement that comes from universities in their websites, advertisements, and banners and indeed in any policy pronouncement or at any other opportunity is how they are committed to quality, what is being done about it and the status of quality management. This paper compares the quality management in the western and American universities and what Asian countries have learnt from both. Their interaction and corresponding accountability to regulating agencies prompt them to align their existence to such needs into their higher educational frameworks.